The Evolution of Blue Carbon: Exploring the Burgeoning Role of Macroalgae in Carbon and Nitrogen Sequestration - Krak, Louie; Heidkamp, C. Patrick (Blue Economy: People and Regions in Transitions, 2022)
The recent attention on Blue Carbon (BC) signals its importance in the burgeoning Blue Economy discourse. BC has traditionally referred to carbon that is
Num Pages: 32
Keywords: dept.egm